A Low‐Frequency Pulsed Magnetic Field Reduces Neuropathic Pain by Regulating NaV1.8 and NaV1.9 Sodium Channels at the Transcriptional Level in Diabetic Rats. Issue 5 (16th May 2021) - Coskun, Cagil; Ocal, Isil; Gunay, Ismail
Abstract : Low‐frequency pulsed magnetic field (LF‐PMF) application is a non‐invasive, easy, and inexpensive treatment method in pain management. However, the molecular mechanism underlying the effect of LF‐PMF on pain is not fully understood. Considering the obvious dysregulations of gene expression observed in certain types of voltage‐gated sodium channels (VGSCs) in pain conditions, the present study tested the hypothesis that LF‐PMF shows its pain‐relieving effect by regulating genes that code VGSCs proteins. Five experimental rat groups (Control, Streptozotocin‐induced experimental painful diabetic neuropathy (PDN), PDN Sham, PDN 10 Hz PMF, and PDN 30 Hz PMF) were established. After the pain formation in PDN groups, the magnetic field groups were exposed to 10/30 Hz, 1.5 mT PMF for 4 weeks, an hour daily. Progression of pain was evaluated using behavioral pain tests during the entire experimental processes. After the end of PMF treatment, SCN9A (NaV1.7 ), SCN10A (NaV1.8 ), SCN11A (NaV1.9 ), and SCN3A (NaV1.3 ) gene expression level changes were determined by analyzing real‐time polymerase chain reaction results. We found that 10 Hz PMF application was more effective than 30 Hz on pain management. In addition, NaV1.7 and NaV1.3 transcriptions were upregulated while NaV1.8 and NaV1.9 were downregulated in painful conditions. Notably, the downregulated expression of the genes encoding NaV1.8 and NaV1.9 were re‐regulated and increased to control level by 10 Hz PMF application. Consequently, it may be deduced that 10 Hz PMF application reduces pain by modulating certain VGSCs at the transcriptional level. © 2021 Bioelectromagnetics Society.